Development of a Library of Thiophene‐Based Drug‐Like Lego Molecules: Evaluation of Their Anion Binding, Transport Properties, and Cytotoxicity. Issue 4 (27th December 2019) - Vieira, Paulo; Miranda, Margarida Q.; Marques, Igor; Carvalho, Sílvia; Chen, Li‐Jun; Howe, Ethan N. W.; Zhen, Carl; Leung, Claudia Y.; Spooner, Michael J.; Morgado, Bárbara; da Cruz e Silva, Odete A. B.; Moiteiro, Cristina; et al.
Abstract: The anion‐binding and transport properties of an extensive library of thiophene‐based molecules are reported. Seventeen bis‐urea positional isomers, with different binding conformations and lipophilicities, have been synthesized by appending α‐ or β‐thiophene or α‐, β‐, or γ‐benzo[ b ]thiophene moieties to an ortho ‐phenylenediamine central core, yielding six subsets of positional isomers. Through 1 H NMR, X‐ray crystallography, molecular modelling, and anion efflux studies, it is demonstrated that the most active transporters adopt a pre‐organized binding conformation capable of promoting the recognition of chloride, using urea and C−H binding groups in a cooperative fashion. Additional large unilamellar vesicle‐based assays, carried out under electroneutral and electrogenic conditions, together with N ‐methyl‐d ‐glucamine chloride assays, have indicated that anion efflux occurs mainly through an H + /Cl − symport mechanism. On the other hand, the most efficient anion transporter displays cytotoxicity against tumor cell lines, while having no effects on a cystic fibrosis cell line. Abstract : Transmembrane carriers : A library of drug‐like molecules, containing thiophene and benzo[ b ]thiophene moieties, has been designed for the transmembrane transport of chloride. Theoretical and experimental investigations have shown that the most active molecules facilitate anion transport through a symport mechanism, taking advantage of the synergy between N−H⋅⋅⋅Cl − and C−H⋅⋅⋅Cl − hydrogen bonds (see scheme).